2008
DOI: 10.1016/j.cell.2008.09.013
|View full text |Cite
|
Sign up to set email alerts
|

RNase P without RNA: Identification and Functional Reconstitution of the Human Mitochondrial tRNA Processing Enzyme

Abstract: tRNAs are synthesized as immature precursors, and on their way to functional maturity, extra nucleotides at their 5' ends are removed by an endonuclease called RNase P. All RNase P enzymes characterized so far are composed of an RNA plus one or more proteins, and tRNA 5' end maturation is considered a universal ribozyme-catalyzed process. Using a combinatorial purification/proteomics approach, we identified the components of human mitochondrial RNase P and reconstituted the enzymatic activity from three recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
632
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 550 publications
(670 citation statements)
references
References 47 publications
17
632
1
1
Order By: Relevance
“…ABAD converts estrone to estradiol, a key antioxidant compound for neurone survival whose intracellular levels are decreased due to the interaction between Aβ and ABAD, a phenomenon that may contribute to Aβ-induced toxicity (Yang et al 2007;Lim et al, 2011). In addition, ABAD is a component of the mitochondrial RNAse P involved in the processing of immature mitochondrial tRNAs (Holzmann et al, 2008).…”
Section: In Alzheimer´s Diseasementioning
confidence: 99%
“…ABAD converts estrone to estradiol, a key antioxidant compound for neurone survival whose intracellular levels are decreased due to the interaction between Aβ and ABAD, a phenomenon that may contribute to Aβ-induced toxicity (Yang et al 2007;Lim et al, 2011). In addition, ABAD is a component of the mitochondrial RNAse P involved in the processing of immature mitochondrial tRNAs (Holzmann et al, 2008).…”
Section: In Alzheimer´s Diseasementioning
confidence: 99%
“…In eukaryotic systems, it has recently been shown that a three-component protein complex from human mitochondria shows RNase P activity (90). This labile complex, whose putative catalytic protein subunit (MRPP3) is the most easily detached, is unique among mitochondrial protein complexes in that is the only one present in the mitochondrial matrix without an endosymbiotic component (91).…”
Section: Exceptions To the Rule: Uncommon Sources For Rnase P/mrp Funmentioning
confidence: 99%
“…A dramatically different model for the human disease state involves HSD10 as an essential component of the RNase P complex (Holzmann et al 2008). This complex is required for 5 ′ cleavage of mitochondrial tRNAs from the polycistronic precursor transcript and contains the proteins MRPP1, MRPP2 (HSD10), and MRPP3, each of which is essential for correct processing in vitro.…”
Section: Hsd10 Is a Multifunctional Enzyme Involved In Mitochondrial mentioning
confidence: 99%